PEMODELAN JEMBATAN RANGKA DENGAN KOMBINASI TIPE RANGKA DITINJAU DARI LENDUTAN DAN BERAT JEMBATAN - Mohammad Musthofa Al Ansyorie; Mohammad Alfin Kirom Mustofa; Madih Tahtal Firdaus Sabila; Nadia Mulia Putri (Prokons: Jurnal Teknik Sipil, 2020)
Abstract The frame bridge structure has several types of frames, each of which has advantages in accordance with its application. Several studies have shown that the comparison between one frame type and another has the advantage of different strengths. In this study an analysis will be carried out by modeling the modified bridge structure truss type and combined with other types to obtain a structure that has the best strengths. The method used in this study is to model the bridge structure with the help of SAP2000 v20 software. The analysis process in this modeling refers to SNI 1725: 2016 concerning load on bridges, BMS (Bridge Management System) in 1992, and several related regulations. The results of modeling analysis show that the K-truss frame is the best frame by looking at the aspect ratio of the bridge, namely the ratio between deflection and weight of each type. The combination of the K-truss frame type and the warren frame type is the best combination of frame types based on the best deflection and weight values. The deflection value for this type of frame combination is -0.416 mm and the ratio value is 6.017. Keywords: modeling, truss bridge, k-truss, combine